PENGELOLAAN MADU HUTAN BERBASIS KEARIFAN LOKAL MASYARAKAT DI DESA SEMALAH DAN DESA MELEMBA KAWASAN DANAU SENTARUM KABUPATEN KAPUAS HULU - Sofia, .; Zainal, Sofyan; Roslinda, Emi (JURNAL HUTAN LESTARI, 2017)
Honey is one of the non-timber forest products (NTFPs). The management of forest honey can be done in a modern and traditional way. The purpose of this study to determine the processes of management of forest honey and the application of local wisdom values in the two villages and different farmer groups. The method used in this study is a survey by interview and questionnaire tools. Analysis of the data used is descriptive qualitative. Management of forest honey maintain sustainable forests as the availability of honey nest and bees feed. The local wisdom is still maintained that the use of honey nest derived from ancestral heritage in the form of tikung, repak and lalau. Keyword: Danau Sentarum Region, Honey Forest, NTFPs, Traditional Wisdom